DIGA-FAM model (differentiation instruction and game-based formative assessment model): students’ needs analysis - Vivi Indriyani; Herlin Triana; Rohaidah Haron; Zaiton Zakarya (ARKA INSTITUTE, 2026)
The growing demand for personalized and engaging learning experiences in digital education highlights the limitations of conventional formative assessments. Many existing assessment practices fail to accommodate learner diversity and sustain motivation. This study aims to analyze students’ needs as a foundation for developing the DIGA-FAM Model (Differentiation Instruction and Game-Based Formative Assessment Model), which integrates differentiated instruction with game-based elements to create adaptive and enjoyable formative assessments. Using a quantitative descriptive approach, data were collected from 104 students through a structured questionnaire and analyzed across six indicators: comfort, interactivity, motivation, differentiation and difficulty level, learning opportunities, and feedback quality. The results show that students prefer formative assessments that are digital-based, interactive, engaging, and tailored to individual learning styles, with opportunities to retry and receive immediate, constructive feedback. These findings emphasize the necessity of developing the DIGA-FAM Model to enhance student engagement, support differentiated learning, improve the effectiveness of formative assessment in classrooms, and fosters meaningful learning experiences.